2018
DOI: 10.20524/aog.2018.0314
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease, functional dyspepsia and irritable bowel syndrome: common overlapping gastrointestinal disorders

Abstract: Several studies have indicated an overlap between gastroesophageal reflux disease (GERD) and various functional gastrointestinal disorders (FGIDs). The overlapping conditions reported have mainly been functional dyspepsia (FD) and irritable bowel syndrome (IBS). The available literature is frequently based on symptomatic questionnaires or endoscopic procedures to diagnose GERD. Rarely, among patients with heartburn, pathophysiological evaluations have been considered to differentiate those with proven GERD fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 123 publications
(153 reference statements)
1
75
0
9
Order By: Relevance
“…Overlap between these conditions is very common, yet pathophysiological reasons for their co-occurrence in the same patient are not well understood [219]. A better understanding of the pathophysiological origin of functional gastrointestinal symptoms related to IBS, GERD and FD may help improve treatment options [220]. In support of this hypothesis, there is empirical evidence to suggest that identification and treatment of a shared pathophysiological origin, H. pylori infection, may resolve overlapping symptoms of IBS, GERD, FD and/or erosive esophagitis in some cases [221].…”
Section: Discussionmentioning
confidence: 99%
“…Overlap between these conditions is very common, yet pathophysiological reasons for their co-occurrence in the same patient are not well understood [219]. A better understanding of the pathophysiological origin of functional gastrointestinal symptoms related to IBS, GERD and FD may help improve treatment options [220]. In support of this hypothesis, there is empirical evidence to suggest that identification and treatment of a shared pathophysiological origin, H. pylori infection, may resolve overlapping symptoms of IBS, GERD, FD and/or erosive esophagitis in some cases [221].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our own preliminary data [2], also mentioned by the authors [1], showed that H. pylori is common in patients with GERD-IBS-FD and/or erosive esophagitis, while H. pylori eradication plus PPI and/or trimebutine regimens offer improvement in HR-QOL, mainly in patients who receive trimebutine. In a subsequent study, we confirmed our preliminary data [6], signifying the effectiveness of trimebutine in these overlapping populations.…”
mentioning
confidence: 90%
“…
In their comprehensive review, de Bortoli et al [1] aimed to discuss the coexistence of gastroesophageal reflux disease (GERD) with irritable bowel syndrome (IBS) and functional dyspepsia (FD) in the same patients and to evaluate the impact of diverse GERD treatments on the health-related quality of life (HR-QOL) of these patients; they mentioned 2 trials that reported resolution of the IBS symptoms in 20-40% of patients after proton pump inhibitor (PPI) therapy [1]. In one of these trials, we mainly observed [2] that trimebutine maleate is effective in the aforementioned overlapping disorders.Relative data indicate that the prevalence of overlaps of FD and/or IBS in GERD, GERD and/or IBS in FD, and GERD and/or FD in IBS is 46.9%, 47.6% and 34.4%, respectively, with worsened HR-QOL [3].
…”
mentioning
confidence: 99%
“…Despite its prevalence, visceral pain is often clinically challenging to delineate its etiology based on symptoms and clinical evaluation alone. Visceral pain is a presenting feature of both organic origin and disorders of gut‐brain interaction, although there is frequent overlap between the two . Organic disorders, where histologically definable pathology is associated with visceral pain include cancer, infectious processes, nephrolithiasis, ischemic disorders, gastro‐esophageal reflux disease, peptic ulceration, cholecystitis, pancreatitis, inflammatory bowel disease (IBD), and viscus perforation.…”
Section: Introductionmentioning
confidence: 99%
“…Visceral pain is a presenting feature of both organic origin and disorders of gut-brain interaction, although there is frequent overlap between the two. 5,6 Organic disorders, where histologically definable pathology is associated with visceral pain include cancer, infectious processes, nephrolithiasis, ischemic disorders, gastro-esophageal reflux disease, peptic ulceration, cholecystitis, pancreatitis, inflammatory bowel disease (IBD), and viscus perforation. However, chronic visceral pain also frequently occurs in the absence of distinct pathology such as in the highly prevalent "nociplastic" conditions of irritable bowel syndrome (IBS) and functional dyspepsia.…”
Section: Introductionmentioning
confidence: 99%